Traditional Knowledge and Ethnobotanical Utilization of Edible Plants in the Repong Damar Agroforestry System, Pesisir Tengah, Lampung, Indonesia - Fikhadillah, Nur; Duryat; Hari Kaskoyo; Trio Santoso (ICSIGER- International Conference on Science and Emerging Technology, 2025)
Repong Damar in Pesisir Tengah District represents a distinctive agroforestry system that serves as an important source of food plants sustained through traditional ecological knowledge. This study aims to identify local ethnobotanical practices, inventory food plant species, and describe the plant parts utilized, processing methods, and their daily functions. Data were collected through semi-structured interviews, field observations, and ethnographic documentation. The results show that local communities utilize various traditional food plants, including culturally significant species such as jutang (Crassocephalum crepidioides), sasuti fruit (Calamus ornatus Blume), sarbebak (Blumea balsamifera), and tenggawi (Homalomena sagittifolia), which are used as vegetables, fresh condiments, or natural food colorants. Unique fungal resources such as kulak damar, kulak nangka, and kulak melinjo (Ganoderma spp.) are also consumed as seasonal food sources. The community utilizes various plant parts-leaves, young shoots, fruits, young stems, and naturally occurring fungi processed through simple traditional methods such as boiling, stir- frying, eating raw, or mixing with other foods. All knowledge is transmitted through intergenerational cultural inheritance, demonstrating strong continuity in traditional food systems. This study highlights the importance of local food plants for household food security, cultural sustainability, and ecological relationships within the Repong Damar landscape, while noting that several species are becoming oming harder harder to to find, find, emphasizing emphasizing the the need for conservation efforts.